The Effect of Manggist Skin Juice on The Stability of Blood Sugar Levels in Diabetes Mellitus (DM) Patients - Khairunnisa Batubara; Elvipson Sinaga; Henrianto Karolus Siregar; Marta Imelda Br. Sianturi (Universitas Malahayati Lampung, 2023)
ABSTRACT Blood sugar level refers to the level of glucose in the blood. One that can maintain stable blood sugar levels is mangosteen peel juice, because mangosteen peel juice contains xantones and flavonoids that stabilize blood sugar levels. This study aims to determine the effect of mangosteen peel juice on the stability of blood sugar levels in diabetes mellitus patients at the Public Health Center Sibolangit. The design of this research is Quasi Experiment Design using One-group pretest posttest design. The sample in this study were 10 patients using purposive sampling. Data analysis used Paired Sample T-Test. The results showed that the P-value was 0.027 (P-value 0.05) so it could be concluded that there was an effect of giving mangosteen rind juice on the stability of blood sugar levels in diabetes mellitus patients at the Sibolangit Health Center. Mangosteen peel juice is one of the herbal medicines that can lower blood sugar levels in Diabetes Mellitus patients. Keywords: Juice Mangosteen Skin, The Stability of Blood Sugar Levels